Spatiotemporal Evolution of Urban Carbon Emissions Based on Night-Time Light Data: A Case Study of Yichang, China - Zhang, Yiwen (International Journal of Natural Resources and Environmental Studies, 2026)
Urban spatial patterns significantly influence carbon emissions, yet research on their precise correlation at the micro-scale remains insufficient. This study integrates DMSP-OLS nighttime light data (2000–2011) and SNPP-VIIRS data (2012–2020) to simulate the spatial distribution of carbon emissions in the main urban area of Yichang. A linear regression model was established between the corrected nighttime light index and the calculated carbon emissions derived from energy consumption data The results indicate a strong positive correlation between night-time light intensity and carbon emissions. Furthermore, the carbon emission center is predominantly concentrated in the Xiling District and diffuses toward the suburbs. Based on these findings, this study proposes urban spatial management strategies aligned with compact city development, including decentralizing core functions, intensive land utilization, and expanding green spaces to facilitate low-carbon transition and sustainable urban development.